FEATURES OF THE DEFINITION OF THE ATTORNEY – CLIENT PRIVILEGE IN US JUDICIAL PRACTICE - Khakimova Kamola (Scholar Express Journals, 2023)
In this article, the author, on the basis of a comparative analysis, studied various approaches and doctrines for determining attorney-client privilege in the United States. In addition, the author gives the historical origin of the concept of attorney-client privilege. The judicial precedents related to the definition of the criteria for attorney-client privilege and its limits are analyzed. Based on the results of studying the features and criteria of attorney-client privilege, the author gives a universal definition of this concept.
Keywords: Advocacy; confidentiality; work product privilege; attorney-client privilege